Circular RNAs in sepsis-induced acute lung injury: emerging mechanisms and therapeutic potential - Liu, Qinghai; Wang, Yiyan; Liao, Haitang; Ren, Dongsheng; Guo, Wenhui; Xu, Jianzhong; Duan, Chenyang; Luo, Zhenchun; Jiang, Wen (Frontiers in Immunology, 2026)
Sepsis-induced acute lung injury (ALI) remains a leading cause of mortality in critically ill patients and is characterized by dysregulated inflammation, immune imbalance, and alveolar–capillary barrier dysfunction. Emerging evidence suggests that circular RNAs (circRNAs), a class of stable and highly conserved non-coding RNAs, play important regulatory roles in inflammatory diseases; however, their contributions to sepsis-associated lung injury have not yet been systematically summarized. In this review, we provide a comprehensive overview of circRNA biogenesis, classification, and regulatory properties, with a particular focus on their context-dependent functions in the septic lung. We discuss how circRNAs participate in the coordination of cell fate decisions, immune responses, and barrier integrity during sepsis, and highlight their potential as diagnostic biomarkers and therapeutic targets. Importantly, we also address current technical and translational challenges, including detection specificity, disease heterogeneity, and limited clinical validation. By integrating mechanistic insights with translational perspectives, this review aims to clarify the emerging role of circRNAs in sepsis-induced ALI and to outline key directions for future research.